2020
DOI: 10.1007/s00018-020-03596-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial miRNAs targeting CAG repeat expansion in ORFs cause rapid deadenylation and translation inhibition of mutant transcripts

Abstract: Polyglutamine (polyQ) diseases are incurable neurological disorders caused by CAG repeat expansion in the open reading frames (ORFs) of specific genes. This type of mutation in the HTT gene is responsible for Huntington’s disease (HD). CAG repeat-targeting artificial miRNAs (art-miRNAs) were shown as attractive therapeutic approach for polyQ disorders as they caused allele-selective decrease in the level of mutant proteins. Here, using polyQ disease models, we aimed to demonstrate how miRNA-based gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 117 publications
4
21
0
Order By: Relevance
“…The strength of this approach is selective elimination of only mutant huntingtin without loss of wild-type huntingtin preserving its physiological function. However, the PRECISION-HD1 and 2 trials were both terminated this year for lack of efficacy ( www.clinicaltrials.gov ; NCT03225833 and NCT03225846 respectively, accessed 2021-10-27), suggesting more work is needed to fully understand the mechanism [25] . Several other ASOs for treatment of neurodegenerative diseases are currently in clinical trials or at preclinical stages of development, as reviewed elsewhere [ 15 , 26 ].…”
Section: Asos Regulating Mrna In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The strength of this approach is selective elimination of only mutant huntingtin without loss of wild-type huntingtin preserving its physiological function. However, the PRECISION-HD1 and 2 trials were both terminated this year for lack of efficacy ( www.clinicaltrials.gov ; NCT03225833 and NCT03225846 respectively, accessed 2021-10-27), suggesting more work is needed to fully understand the mechanism [25] . Several other ASOs for treatment of neurodegenerative diseases are currently in clinical trials or at preclinical stages of development, as reviewed elsewhere [ 15 , 26 ].…”
Section: Asos Regulating Mrna In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, some of the mutant mRNA-targeting oligonucleotides may cause deadenylation. Our recent study, focusing on the mechanisms leading to the allele-selective silencing of HTT , demonstrated that a specific self-duplexing siRNA (sd-siRNA) [ 153 ], which is described as miRNA-like siRNA, caused the rapid deadenylation of the mutant transcript and translational inhibition [ 154 ]. It remains to be investigated how deadenylation is activated in this therapeutic strategy using an endogene of HTT .…”
Section: Discussionmentioning
confidence: 99%
“…They contain specific nucleotide substitutions that result in non-canonical base pairs in interaction with the CAG repeat sequence. Testing of these siRNAs in HD cell models led to the activation of the silencing mechanism preferentially for the mutant allele, due to the binding of multiple RISCs to an extended sequence of repeats [ 28 , 29 ]. Additionally, this strategy is also effective for other polyQ diseases [ 30 , 31 , 32 ].…”
Section: Disease-modifying Strategies For Hdmentioning
confidence: 99%